Der grüne Kakadu: Historisch-kritische Ausgabe - Schnitzler, Arthur (Verlag der Österreichischen Akademie der Wissenschaften, 2020)
Historical-critical edition of Arthur Schnitzler's "Der grüne Kakadu" This edition presents a comprehensive preface analyzing the text genesis, the censoring process as well as the printing history, a transcription of the genetic materials with facsimiles, an edition of the a cesored typescript, a print text with a display of textual variants and a commentary.